Penerapan Pengendalian Internal Terhadap Kecurangan: Sebuah Literatur Review - Benny Marciano; Ardiansyah Syam; Suyanto; Nurmala Ahmar (Universitas Warmadewa, 2021)
Fraud is an intentional deception that can result in losses for organization. Fraud is influenced by the opportunity caused by the weak internal controls in an organization, lack of supervision and abuse of power or authority. This study aims to analyze the effect of internal control on fraud in an organization. The research was conducted using a literature review by examining various previous studies that existed in various electronic databases for searching journals or literature. The keywords used in the literature search included